Attitude, confidence and social norm of Dutch occupational physicians regarding menopause in a work context. (September 2020) - Geukes, Marije; Oosterhof, Henk; van Aalst, Mariëlle P.; Anema, Johannes R.
Highlights: Most occupational physicians do recognize a role for menopause in presenteeism and sickness absence. Generally, Dutch occupational physicians have a positive attitude towards menopause. Occupational physicians perceive lack of knowledge and taboo culture around menopause in the workplace. Occupational physicians express the need for education and a guideline about menopause and work. Abstract: Objective: To explore the attitudes, confidence and social norm of Dutch occupational physicians (OPs) regarding menopause in a work context. Study design: A nationwide cross-sectional exploratory design. An invitation to participate in an online survey was sent to all OPs registered at the Dutch occupational physicians' society (n = 1663). This survey collected data about attitudes, confidence, social norm and current practice of OPs regarding menopause and work. Descriptive statistics and post hoc logistic multivariate analyses were used to evaluate the data. Main outcome measures: Attitudes, confidence and social norms in relation to menopause and work. Results: Data from 267 OPs were analysed. Most OPs do recognize a role for menopause in presenteeism and sickness absence. However, 48% stated that women with bothersome menopausal symptoms are 'not sick' and 'just experiencing symptoms of a normal physiological process'. Over 56% of OPs find it difficult to assess the relationship between menopausal symptoms and work ability, and 63% to report menopause as a diagnosis in the context of a sick leave certification. Over 56% of OPs acknowledge that talking about menopause in the workplace is a taboo. A positive attitude towards menopause (OR 1.11, 95% CI 1.02-1.20) and greater confidence (OR 1.22, 95% CI 1.14-1.31) were associated with significantly higher levels of diagnosing menopause in sick leave certification. Conclusions: Dutch OPs generally have a positive attitude towards menopause, but perceive a lack of knowledge and a taboo culture around menopause in a work context. They indicate a need for education and a guideline on menopause and work.